THE SYMBOL AND MEANING A SEMANTIC STUDY - Yousif, Hajar Kamal (Journal of Duhok University, 2018)
The present research entitled "The symbol and meaning a semantic study "delas with the symbole and its types and the relationship of signifier and signified with linguistic and non-linguistic  symbols. The research is descriptive one and consists of two chaopters: the fist cgapter identifies symbol and its types، while the second chapter studies the relationship between symbol and meaning. The researcher has come up with findings and the most important one is that the relationship between linguistic symbols is not likeness while the relationship between nonlinguistic symbol is likeness relationship.